Effect of water temperature on flow regimes and reynolds number in a passive natural circulation cooling system - Setiawan, Putut Hery; Pamitran, Agus Sunjarianto; Yuliaji, Dwi; Pamungkas, Adhika Enggar; Budiman, Arif Adtyas; Amelia, Almira Citra; Maryadi, Shendy Akbar; Irwansyah, Ridho; Juarsa, Mulya (Jurnal Polimesin, 2025)
Natural circulation flow is an important phenomenon of passive cooling systems in nuclear reactor thermal management during accidents. This experimental study investigates the effect of varying water temperatures on flow regimes and Reynolds number within a passive natural circulation system. The research was conducted using a rectangular TP-loop (FASSIP-04 Ver.2) made of 1-inch SS304 pipe, 6 m high and 1.32 m wide. The water temperature setting was varied at 45°C, 55°C, 65°C, and 75°C, with a heating power of 4.2 kW, and the cooling tank was maintained at 10°C. Observations were made during transient heating, steady-state (for 3 hours), and transient cooling phases. Results show that increasing the heating tank temperature reduces fluid density and viscosity, thereby enhancing buoyancy-driven flow. This led to a transition in flow regimes from laminar to turbulent as the temperature increased. The Reynolds number increased by 169.38% when the water temperature was raised from 45°C to 75°C. Unstable flow behaviour, including fluctuating amplitudes and frequencies, was observed—characteristic of natural circulation dynamics. The study confirms a strong correlation between thermal variation and flow regime transition, providing insights into the performance of passive cooling systems under varying thermal loads.